Dampak Keputusan Investasi, Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan Sektor Pertambangan di Indonesia: Kajian Mediasi Resiko Perusahaan - Rofi'i, Yulianto Umar (Jurnal EMT KITA, 2023)
This study aims to study the impact of investment decisions, financing decisions and dividend policies on firm value in the mining sector in Indonesia, with firm risk as the mediating variable. The subject of this study includes companies listed on the Indonesia Stock Exchange in the period 2018-2023. Investment decisions that have a direct impact on corporate value, focus on decisions that reflect future investment opportunities, such as introducing new products, expanding existing products, replacing replacement of equipment or facilities, research, development, and exploration. The results of the deterministic analysis show that the coefficient of determination (R^2) is 0.955, indicating that only about 95.5% of the variation in firm value (book value) can be explained simultaneously. by investment decisions, financing decisions and dividend policies. This means that the company's risk is not directly affected by these variables. Furthermore, the analysis results show that the coefficient of determination (R^2) is 0.041, indicating that only about 4.1% of the variation in firm risk can be explained by variations in investment decisions. investment, financing decisions and dividend policy. The remainder, about 96.9%, shows that firm risk does not play a mediating role between investment decisions, financing decisions, dividend policy, and firm value. In other words, firm risk does not partially link these variables to firm value. The results of this study indicate that although investment decisions, financing decisions and dividend policies have a significant impact on firm value, firm risk does not play a mediating role in the relationship. relationship between these variables.